Wireless HDLC Protocol for Energy-Efficient Large-Scale Linear Wireless Sensor Networks. (17th April 2014) - Toma, Daniel Mihai; del Rio, Joaquin; Mànuel, Antoni
Wireless sensor networks (WSNs) have been widely recognized as a promising technology that can enhance various aspects of infrastructure monitoring. Typical applications, such as sensors embedded in the outer surface of a pipeline or mounted along the supporting structure of a bridge, feature a large-scale linear sensor arrangement. In this paper, we propose a new bidirectional wireless communication scheme, based on the high-level data link control (HDLC) standard, for devices with short-range transmission capabilities for linear sensor topology. By applying for the first time a standard data layer along with a time division multiple access (TDMA)-based medium access control (MAC) and time synchronization technique specifically designed for the linear topology, we address the interoperability problem with guaranteed energy efficiency and data link performance in linear sensor topology. The proposed Wireless HDLC supports half-duplex communication, point to point (peer to peer), and multipoint networking.